2016
DOI: 10.15252/embj.201592532
|View full text |Cite
|
Sign up to set email alerts
|

Sororin actively maintains sister chromatid cohesion

Abstract: Cohesion between sister chromatids is established during DNA replication but needs to be maintained to enable proper chromosome-spindle attachments in mitosis or meiosis. Cohesion is mediated by cohesin, but also depends on cohesin acetylation and sororin. Sororin contributes to cohesion by stabilizing cohesin on DNA. Sororin achieves this by inhibiting WAPL, which otherwise releases cohesin from DNA and destroys cohesion. Here we describe mouse models which enable the controlled depletion of sororin by gene d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 81 publications
(200 reference statements)
7
125
0
1
Order By: Relevance
“…As SMC3 is the most studied and discussed target of ESCO1/2 (Minamino et al 2015;Ladurner et al 2016), we next sought to address the effects of defective or The results were confirmed with lysates from an independent biological experiment. (C) Growth curves.…”
Section: Smc3-k105 K106 Acetylation Is Not Singularly Responsible Fomentioning
confidence: 98%
See 4 more Smart Citations
“…As SMC3 is the most studied and discussed target of ESCO1/2 (Minamino et al 2015;Ladurner et al 2016), we next sought to address the effects of defective or The results were confirmed with lysates from an independent biological experiment. (C) Growth curves.…”
Section: Smc3-k105 K106 Acetylation Is Not Singularly Responsible Fomentioning
confidence: 98%
“…Acetyl-mimicking mutations of K105 and K106 sites of SMC3 reduce cohesin mobility (Ladurner et al 2016), but whether SMC3 acetylation underlies the essential function of ESCO1 and ESCO2 in proliferation (see Fig. 2C) and whether that essential function is linked to SCC are not known.…”
Section: Smc3-k105 K106 Acetylation Is Not Singularly Responsible Fomentioning
confidence: 99%
See 3 more Smart Citations